2004
DOI: 10.1002/chin.200410174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Steroidal Oxazoles and Thiazoles.

Abstract: Synthesis of New Steroidal Oxazoles and Thiazoles. -Some new steroidal oxazoles (III) and thiazoles (V) are synthesized by a simple condensation of steroidal α-bromoketones (I) with urea and thiourea, respectively. -(SHAMSUZZAMAN*; SALIM, A.; AKRAM, M. K.; SALEEM, K.; SIDDIQUI, N.; Indian J. Chem., Sect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…Comparative results of previously reported compounds ( 5 and 6 ) in terms of yield and reaction period are given. All spectral and analytical data for compounds 5 and 6 were identical with those previously reported (Shamsuzzaman et al, 2003[ 22 ]). Comparison of conventional and microwave syntheses of 4 - 6 : (1) conventional procedure reported (Shamsuzzaman et al, 2003[ 22 ]); compound 5 , yield: 90 %, time: 1 h, compound 6 , yield: 85 %, time: 1 h, (2) microwave procedure; compound 4 , yield: 85 %, time: 2.5 min, compound 5 , yield: 93 %, time: 2.0 min, compound 6 , yield: 90 %, time: 3.0 min, respectively.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Comparative results of previously reported compounds ( 5 and 6 ) in terms of yield and reaction period are given. All spectral and analytical data for compounds 5 and 6 were identical with those previously reported (Shamsuzzaman et al, 2003[ 22 ]). Comparison of conventional and microwave syntheses of 4 - 6 : (1) conventional procedure reported (Shamsuzzaman et al, 2003[ 22 ]); compound 5 , yield: 90 %, time: 1 h, compound 6 , yield: 85 %, time: 1 h, (2) microwave procedure; compound 4 , yield: 85 %, time: 2.5 min, compound 5 , yield: 93 %, time: 2.0 min, compound 6 , yield: 90 %, time: 3.0 min, respectively.…”
Section: Resultssupporting
confidence: 70%
“…Microwave-promoted reactions were carried out using a Laboratory Grade Microwave oven fixed with a temperature monitoring sensor. Steroidal keto-oximes (1-3) were prepared according to published methods (Shamsuzzaman et al, 2003[ 22 ]; Soppee et al, 1964[ 24 ]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahmad 38 has reported a similar set of title compounds starting from the same material but with a different solvent, methanol but provided no satisfactory mechanism. However, Shamsuzzaman et al 39 reported different steroidal thiazoles starting from similar precursor using ethanol as a solvent with a refluxing period of 2-3 hrs. …”
Section: Scheme1 Synthesis Of Fused Steroidal Thiazolesmentioning
confidence: 99%